Myosin VI is expressed in developing ovarian follicles in Drosophila but is not essential for effective oogenesis - Lenartowski, Robert; Ostrowski, Jakub; Suwińska, Anna; Richert, Anna; Zakrzewski, Przemysław; Izdebska, Magdalena; Arendt, Wioletta; Miller, Kathryn G.; Lenartowska, Marta (Frontiers in Cell and Developmental Biology, 2025)
Myosin VI is the only actin-based motor known to move toward the minus end of actin filaments. This protein is involved in many different cellular processes, such as endocytosis, autophagy, secretion, and regulation of actin organization and dynamics. Myosin VI has also been suggested to play an important role in collective migration of border cells and egg chamber development during Drosophila oogenesis. Here we show for the first time that myosin VI is expressed in Drosophila germarium as well as in early ovarian follicles, especially in the developing oocyte. As oogenesis progresses, the level of myosin VI in maturing egg chambers decreases, but this protein is present both in the nascent border cell cluster, during its delamination from the epithelium, and then during the early stages of border cell migration. However, we demonstrate that myosin VI deficiency in border cells, or even complete lack of this protein in myosin VI mutant do not inhibit border cell migration. Moreover, deficiency/lack of myosin VI does not cause any serious defects in ovarian morphology, egg chamber morphogenesis, oogenesis, and egg development. Thus we conclude that myosin VI is not a key player in Drosophila oogenesis.